2013
DOI: 10.3402/ijch.v72i0.21066
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Alaska Native paediatric oral health disparities: a systematic review of oral health interventions and a case study on multilevel strategies to reduce sugar-sweetened beverage intake

Abstract: BackgroundTooth decay is the most common paediatric disease and there is a serious paediatric tooth decay epidemic in Alaska Native communities. When untreated, tooth decay can lead to pain, infection, systemic health problems, hospitalisations and in rare cases death, as well as school absenteeism, poor grades and low quality-of-life. The extent to which population-based oral health interventions have been conducted in Alaska Native paediatric populations is unknown.ObjectiveTo conduct a systematic review of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 39 publications
1
44
0
Order By: Relevance
“…33 Nonetheless, community-centered multilevel interventions to reduce sugar-sweetened beverage intake among Alaska Native children were deemed promising. 33 Another systematic review was conducted on the influence of family environment on children’s oral health.…”
Section: Social Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Nonetheless, community-centered multilevel interventions to reduce sugar-sweetened beverage intake among Alaska Native children were deemed promising. 33 Another systematic review was conducted on the influence of family environment on children’s oral health.…”
Section: Social Interventionsmentioning
confidence: 99%
“…33 Nonetheless, community-centered multilevel interventions to reduce sugar-sweetened beverage intake among Alaska Native children were deemed promising. 33 Another systematic review was conducted on the influence of family environment on children’s oral health. 34 The authors concluded that since parents’ dental habits influence their children’s dental habits, special attention should be given to the entire family, not only to prevent oral disease, but to improve quality of life.…”
Section: Social Interventionsmentioning
confidence: 99%
“…range from genetic and biological to cultural, behavioral, social, and administrative (Patrick et al, 2006;Fisher-Owens et al, 2007;Chi, 2013;Lee and Divaris, 2014). High-impact research is being conducted at all these levels.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors that trigger dental caries are poor oral hygiene, frequent ingestion of sugary foods, etc. The main symptoms of caries are acute pain, inflammation, increased sensitivity to food or cold or hot drinks, bad breath and tooth loss [18].…”
Section: Literature Review:-mentioning
confidence: 99%
“…Thus, the control of the presence of microorganisms in the oral cavity influencing the caries process, or being influenced by organic salivary, immunological and chemotherapeutic factors, should not be considered for the establishment of prevention strategies, and the simple presence of microorganisms in the oral Cavity, whether in saliva or plaque, is not a factor that determines the onset of disease caries [17][18][19][20].…”
Section: Literature Review:-mentioning
confidence: 99%